2015
DOI: 10.1039/c5ra05422b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement effect of essential oils from the fruits and leaves of Alpinia oxyphylla on skin permeation and deposition of indomethacin

Abstract: Essential oils from plants are gaining increasing attention as potential chemical penetration enhancers. This study aimed to investigate the enhancement effect of essential oils from the fruits and leaves of Alpinia oxyphylla on skin permeation and deposition of indomethacin. In vitro permeation experiments were performed in Franz-type cells through rat skin, and the amount of drug passing through into the receptor phase was analyzed by ultra performance liquid chromatography-photodiode array (UPLC-PDA). Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Of these, nootkatone (10.23–12.30%), p-cymene (5.88–8.77%), alloaromadendrene (8.72–10.34%), aristolene epoxide (3.26–4.56%), α-selinene (1.87–2.43%), α-guaiene (1.85–2.31%), α-panasinsen (1.78–2.20%), caryophyllene oxide (1.85–2.49%), gingerol (2.04–2.94%) were found to be the principal chemical constituents. Similar results have been reported in other studies (Feng et al 2015 ; Miao et al 2015 ). As shown in Additional file 1 : Figure S3 and Table 2 , mold infection had small effects on the composition of volatile compounds in A. oxyphylla .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Of these, nootkatone (10.23–12.30%), p-cymene (5.88–8.77%), alloaromadendrene (8.72–10.34%), aristolene epoxide (3.26–4.56%), α-selinene (1.87–2.43%), α-guaiene (1.85–2.31%), α-panasinsen (1.78–2.20%), caryophyllene oxide (1.85–2.49%), gingerol (2.04–2.94%) were found to be the principal chemical constituents. Similar results have been reported in other studies (Feng et al 2015 ; Miao et al 2015 ). As shown in Additional file 1 : Figure S3 and Table 2 , mold infection had small effects on the composition of volatile compounds in A. oxyphylla .…”
Section: Resultssupporting
confidence: 92%
“…In addition, A. oxyphylla is also consumed as a food in China. Phytochemical studies have indicated that it contains volatile oils, polysaccharides, flavonoids and diarylheptanoids (Li et al 2013 ; Feng et al 2015 ; Zhao et al 2013 ). Because it is widely distributed in tropical and subtropical regions, A. oxyphylla can become moldy during its growth, harvesting, processing and storage.…”
Section: Introductionmentioning
confidence: 99%
“…A still further example is the permeation effects of isopulegol, 1,8‐cineole and limonene, menthol and Alpinia oxyphylla Miq . oil …”
Section: Other Natural Monoterpene Biological Activitiesmentioning
confidence: 99%
“…Alpiniae Oxyphyllae Fructus ("Yi-Zhi-Ren" in Chinese), the mature fruit of Alpinia oxyphylla Miq., is a famous traditional Chinese medicine (TCM) [1]. Alpiniae have reported that Alpiniae Oxyphyllae Fructus has the pharmacological activities of protecting the kidneys, protecting the nervous system, regulating immune function, regulating gastrointestinal function, anti-oxidation, anti-inflammatory, and protecting the cardiovascular system [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, it has been extensively used as a dietary and medicinal substance in China for thousands of years [2,3]. Numerous studies have reported that Alpiniae Oxyphyllae Fructus has the pharmacological activities of protecting the kidneys, protecting the nervous system, regulating immune function, regulating gastrointestinal function, anti‐oxidation, anti‐inflammatory, and protecting the cardiovascular system [4–12].…”
Section: Introductionmentioning
confidence: 99%